Analisis Pengaruh Online Advertising dan Celebrity Endorser tehadap Minat Beli dan Dampaknya pada Keputusan Pembelian Konsumen Shopee - M. Arif Mutawakil; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research aims to analyze the influence of Online Advertising (X1), Celebrity Endorser (X2), on Purchase Intention (Z), and consequently on Purchase Decision (Y) (Study on Shopee Consumers, Active Student of the Faculty of Economics, University of Bachelor of Science, Tamansiswa). This type of research is quantitative research, by taking a sample of Shopee consumers, students of the Faculty of Economics, Tamansiswa University of Bachelor of Economics, as many as 93 respondents. Drawing illustrations using purposive sampling method, collecting information by means of a questionnaire survey. Information is processed using SPSS. Test results in this research, it proves that the Online Advertising and Celebrity Endorser variables positively and significantly affect Purchase Interest and support Purchase Decisions for Shopee consumers.Based on the results of this study the effect of online advertising on purchase intention based on the online advertising variable subtest is 4.093 and a significance value of 0.000 which is smaller than 0.05 (0.000 <0.05). The influence of celebrity endorsers on purchase intention is based on 2.199 subtests of the celebrity endorser variable and a significance value of 0.003 so it is smaller than 0.05 (0.003 <0.05). Based on the subtest, the variable value of buying interest on purchasing decisions is 3.845 and a significance value of 0.000 which is less than 0.05. The online advertising variable on purchasing decisions is 2.342 with a significance value of 0.030 which means less than 0.05 (0.030 <0.05), and the influence of celebrity endorsers on purchasing decisions based on the celebrity endorser variable subtest is 2.543 with significance. the value of 0.021 is more or less than 0.05 (0.021 <0.05). Keywords: Online Advertising, Celebrity End\orser, Purchase Interest, Purchase Decision